Suspected sevoflurane-associated hypersensitivity reaction in a pediatric patient: a case report - Işın Gençay; Yiğit Ali Keleş; Gülçin Aydın; Kevser Peker; Esra Polat; Cem Gençay (Eurasian Journal of Anesthesiology and Intensive Care, 2026)
Perioperative hypersensitivity reactions are uncommon but potentially serious complications that require early recognition and appropriate management. Although numerous drugs and substances used during anesthesia may cause hypersensitivity reactions, reactions associated with volatile anesthetic agents are extremely rare. We present a six-year-old, who developed an acute cutaneous hypersensitivity reaction approximately five minutes after inhalational induction with sevoflurane. Erythema and swelling developed over the trunk without respiratory distress, oxygen desaturation, hemodynamic instability, or other systemic manifestations. Sevoflurane was discontinued, the anesthesia circuit was changed, and 100% oxygen was administered. Following establishment of intravenous access, crystalloid fluid and pharmacological treatment with an antihistamine, corticosteroid, and inhaled bronchodilator were administered. The clinical findings improved without progression and surgery was subsequently completed. This case highlights that hypersensitivity reactions may rarely occur during inhalational induction with sevoflurane and may pose a particular challenge when intravenous access has not yet been established.